Analysis of the e-learning innovation process in higher education - Lin, Chih-Cheng (2010)
E-Learning perhaps is the exciting topic related to higher education in the current decade. Large numbers of researchers devote their enthusiasm to this area. The early days of E-Learning were product-driven, and the dialogue about E-Learning took place primarily among vendors who were heavily funded by investment capital. Most of the E-Learning vendors promoted their technology, but less attention was paid to the issues surrounding implementation or to the usage of E-Learning by the end users. However, the behaviour of end users or of the organizations which had introduced E-Learning should be the main concern of an innovation in the management process. Included in an entire E-Learning development strategy should be a detailed analysis and action plan to obtain a comprehensive overview of three aspects of innovation processes: organizational, technological, and products/services. A successful E-Learning launch should also pay close consideration to all of the interactions during the triple innovation process, a proposal which will be addressed in this research.